ANALYSIS OF FACTORS AFFECTING STOCK PRICES WITH MANAGERIAL OWNERSHIP AS A MODERATING VARIABLE IN INDUSTRIALS SECTOR MANUFACTURING COMPANIES LISTED ON THE STOCK EXCHANGE INDONESIA PERIOD 2018-2022 - Edi Santana Putra; Nisrul Irawati; Syahyunan (CV. Radja Publika, 2024)
This research aims to examine the influence of Debt to Equity Ratio, Net Profit Margin, Return on Equity, Earning per Share, Return on Assets and Rupiah Exchange rate on share prices with Managerial Ownership as a Moderating variable in Industrial sector manufacturing companies listed on the Indonesian Stock Exchange.The research carried out is a type of causal associative research. This research was conducted at the Indonesian Stock Exchange, North Sumatra Representative, Jalan Ir. H. Juanda Baru No. A5-A6, Medan. North Sumatra. The observation period starts from 2018-2022, secondary data collection for this research was carried out by looking at each company's annual report on the websitewww.idx.co.id. September 2023 was chosen by researchers as the research time period. The population used in this research is industrial manufacturing companies listed consecutively on the IDX with the observation year 2018-2022, namely 56 companies. According to these criteria, it can be seen that the number of samples used in this research was 20 companies. So the number of observations in this research is: 5 years x 20 samples = 100 observation data. With the results, DER has a negative and insignificant effect on share prices in Industrials Sector Manufacturing Companies listed on the Indonesia Stock Exchange. NPM has a negative and insignificant effect on Share Prices in Industrials Sector Manufacturing Companies listed on the Indonesia Stock Exchange. ROE has a negative and insignificant effect on share prices in industrial manufacturing companies listed on the Indonesian Stock Exchange. EPS has a negative and insignificant effect on share prices in industrial manufacturing companies listed on the Indonesian Stock Exchange. ROA has a positive and significant influence on share prices in industrial manufacturing companies listed on the Indonesian Stock Exchange. The Rupiah exchange rate has a negative and insignificant effect on share prices in industrial manufacturing companies listed on the Indonesian Stock Exchange. Managerial Ownership has a positive and insignificant effect on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesian Stock Exchange. Managerial ownership is unable to moderate the influence of DER on share prices in industrial manufacturing companies listed on the Indonesian Stock Exchange. Managerial Ownership is unable to moderate the influence of NPM on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange. Managerial Ownership is able to moderate the influence of ROE on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange. Managerial Ownership is able to moderate the influence of EPS on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange. Managerial Ownership is able to moderate the influence of ROA on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange. Managerial Ownership is unable to moderate the influence of the Rupiah Exchange Rate on Share Prices in Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange